Residential burglary: main results of a study in Germany - Wollinger, Gina Rosa (2017)
Unlike most criminal offenses in Germany, the rate of residential burglary has significantly increased since 2006. This high number of burglary cases is contrary to a very low rate of suspects actually identified by the police. However, official statistics indicate that individual districts in Germany strongly differ regarding the frequency rate as well as the number of suspects. Hereby, the Criminology Research Institute of Lower Saxony conducted a comprehensive study on residential burglary regarding the characteristics of burglary offenses, the situation of victims, criminal investigations and legal proceedings, as well as the characteristics of offenders. Written surveys were completed with victims of burglary (N=1,329) and criminal files were analyzed (N=3,668). The present paper represents the main results of this research project.